Nearly ideal vertical GaN Schottky barrier diodes with ultralow turn-on voltage and on-resistance. (31st March 2017) - Ren, Bing; Liao, Meiyong; Sumiya, Masatomo; Wang, Linjun; Koide, Yasuo; Sang, Liwen
Abstract: Vertical Schottky barrier diodes (SBDs) were fabricated from the metal–organic chemical vapor deposition (MOCVD)-grown GaN epitaxial layer on free-standing GaN substrates. It was found that the quality of GaN drift layers and SBD properties were strongly dependent on the growth rates. The step-flow surface morphology, near-unity ideality factor ( n ∼ 1.04), and high Schottky barrier height (∼0.97 eV) were achieved at a relatively low growth rate of 2.61 µm/h. An extremely low turn-on voltage (0.73 V), together with a low on-resistance of 0.72 mΩ·cm 2, was obtained.